IbM KELOMPOK USAHA “WANITA KREATIF” DI DESA TEMPOS KECAMATAN GERUNG - Baiq Ertin Helmida; Nizar Hamdi; Baiq Kisnawati (Sekolah Tinggi Ilmu Ekonomi AMM, 2016)
The purpose of this activity is to: 1) improving the understanding of the formulation and the benefits of business planning (business plan) for business management and strategic business development plan; 2). increase understanding of partner management and financial administration; 3) Improving the understanding and skills of partners of the production process to produce products that vary with the taste delicious, attractive and hygienic by using a more modern / advanced. The results of the program are (1) Partners have adequate equipment; (2) To increase the knowledge andskills of business group partners plan business development (business plan); (3) Increasing the knowledge and skills of business groups in the financial management of business partners; (4) There is an increasing skills in the production process that will produce a quality product, varied, interesting, delicious taste, hygienic, kosher for consumption and be able to take advantage of the abundant raw material production in the local area (local food); (5) Partners have brands / labels with innovative design, good packaging for ready for the market; (6) The increase in production and sales volume of more than 30%; (7) The creation of an independent businesswoman and creative a number of 7 people